Moral Education and its Impressionable Factors - Xakimovich, Amanlaev Abdurasul; Pulatovna, Ergasheva Maxsuda (European Journal of Life Safety and Stability (2660-9630), 2021)
This article focuses on the moral education of young people and its impressionable factors. It is also stated that joint activities of neighborhood, family, school and community organizations play an important role in moral education of youth.